Systemic and Ocular Anti-Inflammatory Mechanisms of Green Tea Extract on Endotoxin-Induced Ocular Inflammation - Chu, Kai On; Chan, Kwok Ping; Yip, Yolanda Wong Ying; Chu, Wai Kit; Wang, Chi Chiu; Pang, Chi Pui (Frontiers in Endocrinology, 2022)
Introduction: Green tea extract (GTE) alleviated ocular inflammations in endotoxin-induced uveitis (EIU) rat model induced by lipopolysaccharide (LPS) but the underlying mechanism is unclear. Objectives: Investigate systematic and local mechanisms of the alleviation by untargeted metabolomics using liquid chromatography-tandem mass spectrometry. Methods: Sprague-Dawley rats were divided into control group, LPS treatment group, and LPS treatment group treated with GTE two hours after LPS injection. The eyes were monitored by slip lamp and electroretinography examination after 24 hours. The plasma and retina were collected for metabolomics analysis. Results: In LPS treated rats, the iris showed hyperemia. Plasma prostaglandins, arachidonic acids, corticosteroid metabolites, and bile acid metabolites increased. In the retina, histamine antagonists, corticosteroids, membrane phospholipids, free antioxidants, and sugars also increased but fatty acid metabolites, N-acetylglucosamine-6-sulphate, pyrocatechol, and adipic acid decreased. After GTE treatment, the a- and b- waves of electroretinography increased by 13%. Plasma phosphorylcholine lipids increased but plasma prostaglandin E1, cholanic metabolites, and glutarylglycine decreased. In the retina, tetranor-PGAM, pantothenic derivatives, 2-ethylacylcarinitine, and kynuramine levels decreased but anti-oxidative seleno-peptide level increased. Only phospholipids, fatty acids, and arachidonic acid metabolites in plasma and in the retina had significant correlation (p < 0.05, r > 0.6). Conclusions: The results showed GTE indirectly induced systemic phosphorylcholine lipids to suppress inflammatory responses, hepatic damage, and respiratory mitochondrial stress in EIU rats induced by LPS. Phospholipids may be a therapeutic target of GTE for anterior chamber inflammation.